Comparing two methods for delivering clinical trial informed consent information to older adults: singular versus stepped approach. (December 2018) - O'Hare, Fleur; Flanagan, Zachary; Nelson, Mark; Curtis, Andrea; Heritier, Stephane; Spark, Simone; Zoungas, Sophia
Background: Adapting the informed consent process to the needs of older adults may enhance engagement and willingness to participate in a clinical trial. A key aspect of the process is being provided with written clinical trial information and consent documents and having an opportunity to discuss the information with the researcher. However, there are no guidelines on the most appropriate method for delivering this information to older adults and it is not known whether the delivery method is a facilitator or barrier towards clinical trial participation. Aims: To compare two delivery methods of informed consent on recruitment, refusal to continue and randomisation rates in a general practice-based clinical trial involving older adults. Methods: In a matched cohort sub-study as part of the STAtins in Reducing Events in the Elderly clinical trial, 520 participants were allocated into two groups by age, gender and attending general practice location, to receive the trial information and consent form in the mail (Method 1) prior to the first baseline visit or in person (Method 2) at the visit where a comprehensive informed consent process took place. Results: Compared with Method 1, potential participants assigned to Method 2 were more likely to agree to attend the first baseline screening visit (refusal rate 20% vs 13.5%, respectively, p = 0.05). However, there was no significant difference in the proportion of participants recruited into the trial by providing written informed consent at the first baseline screening visit. For each informed consent delivery method, similar proportions of participants refused to take part in the trial by the end of the screening phase. Randomisation rates in the two groups were also similar. Time to conduct the informed consent procedure took significantly longer with Method 2 compared with Method 1 (median time 20 vs 15 min, respectively, p < 0.01). Interest in the research trial topic was the main reason cited (33.4%) for considering trial participation. Conclusion: Later delivery of informed consent documents to potential participants in this trial was associated with a small increase in attendance at the first, in person, screening visit. However, the randomisation rate of participants into the trial was not affected by the method and timing of delivery of informed consent information. Similar randomisation rates occurred whether potential participants were mailed informed consent documents prior to the first in person screening visit or were given the information at the screening visit.